2015
DOI: 10.1001/jamaneurol.2015.2154
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of Generic Glatiramer Acetate in Multiple Sclerosis

Abstract: for the Glatiramer Acetate Clinical Trial to Assess Equivalence With Copaxone (GATE) Study Group IMPORTANCE The patents for the first approved treatments for relapsing-remitting multiple sclerosis are expiring, creating the opportunity to develop generic alternatives.OBJECTIVE To evaluate in the Glatiramer Acetate Clinical Trial to Assess Equivalence With Copaxone (GATE) study whether generic glatiramer acetate (hereafter generic drug) is equivalent to the originator brand glatiramer acetate (hereafter brand d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 25 publications
0
62
0
5
Order By: Relevance
“…[174][175][186][187][188][189][190][191][192][195][196][197][198][199][200]213,216,[219][220][222][223][224] Studies that reported methods of allocation concealment (the concealment of study allocation before the beginning of assigned treatment) were also judged to be at low risk of bias (n = 22/35), 171,[174][175]181,[188][189][190][191][195][196][198][199]207,213,[216][217][219][220][221][222][223][224] with the exception of one study that used open allocation. 170 All studies citing central allocation were judged as having a low risk of bias.…”
Section: Risk In Randomisation or Allocation Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…[174][175][186][187][188][189][190][191][192][195][196][197][198][199][200]213,216,[219][220][222][223][224] Studies that reported methods of allocation concealment (the concealment of study allocation before the beginning of assigned treatment) were also judged to be at low risk of bias (n = 22/35), 171,[174][175]181,[188][189][190][191][195][196][198][199]207,213,[216][217][219][220][221][222][223][224] with the exception of one study that used open allocation. 170 All studies citing central allocation were judged as having a low risk of bias.…”
Section: Risk In Randomisation or Allocation Methodsmentioning
confidence: 99%
“…170 All studies citing central allocation were judged as having a low risk of bias. 171,175,190,198,207,213,[216][217][219][220]222 Risk in methods of blinding…”
Section: Risk In Randomisation or Allocation Methodsmentioning
confidence: 99%
See 3 more Smart Citations